Accounting Remodelling pada Usaha Mikro Kecil dan Menengah (UMKM) yang Potensial Dibiayai oleh Perbankan - Dewi, Resti Kartika (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research aims to redesign the accounting model for micro, small and medium enterprises (MSMEs) that is suitable for banking financing. The population in this research is MSMEs in Mataram City which have the potential to be financed by banking according to the 2023 Bank Indonesia MSMEs profile database. The sample was determined using a judgment sampling method so that MSMEs with the individual business criteria "Nasi Uduq" were selected as the research location. The main subjects in this research are MSMEs business owners. Data collection methods were carried out by interviews, observation and documentation. The data analysis technique was carried out using descriptive analysis.  The research results show that accounting remodeling is very important in increasing the readiness and ability of MSMEs to obtain financing from banks. The application of the accounting model carried out by MSMEs "Nasi Uduq" in the recording aspect is still at level 1 stage, namely recording transactions which are still done manually, not yet separating recording based on type of transaction, and not yet separating recording between business transactions and personal transactions. In the transaction classification aspect, ledger posting has not been carried out, in the transaction summarization aspect, the trial balance has not been prepared or adjusting journal entries have been carried out and in the financial reporting aspect it has not been carried out comprehensively and does not reflect the actual conditions.